Modeling quality of life of Ho Chi Minh City dwellers - Huynh, Vy Dang Bich; To Nguyen, Quyen Le Hoang Thuy; Nguyen, Tram Huynh Mai; Nguyen, Phong Thanh; Dang, The Thi Ngoc (International Journal of Public Health Science (IJPHS), 2023)
Quality of life (QoL) has received more and more attention from scholars and researchers from various fields such as healthcare, philosophy, psychology, sociology, and especially economics after many decades of focusing on income. However, researchers have faced many challenges to gain the proper measurement of QoL due to the contextually based concept. This study employs the primary data conducted in Ho Chi Minh City including 500 observations in 2022, with the application of partial least squares structural equation modeling (PLS-SEM) to construct a hierarchical model to measure the QoL of the dwellers in Ho Chi Minh City. The empirical model supports the multi-level hierarchical structure of the QoL. The statistically significant contribution of economic, social, and environmental dimensions in the integrated index has been confirmed. The environmental component shares the highest weight, followed by the economic factor. The social aspect contributes the least share in the quality- of-life index. Further analysis of the sub-criteria in each dimension has been made. The findings implicitly suggest the policy concentration on sustainable factors enhancement to raise the QoL. It was a milestone for policy makers to switch the focus from material to non-material factors in the life quality model in Vietnam.